RANCANG BANGUN SISTEM INFORMASI AKUNTANSI PEMBELIAN BAHAN BAKU SECARA KREDIT PADA PT. PROMETAMA SARANA GRAHA TANGERANG - Hoiriah Hoiriah; Gesti Sri Malinda; Viansie Rahmadinie (Yayasan Akrab Pekanbaru, 2019)
Now a days information technology is not only rapidly developing, but also often changes very quickly. Almost every second new discoveries are always found with the aim of improving or perfecting the previous technology. In the developca of economics and technology when the use of computers feels more needed in order to facilitate human work and be more time efficient. PT. Prometama Sarana Graha requires a system that can support data processing of raw material purchases. For this reason, the author tries to make a final assignment regarding the design of accounting information systems for purchasing raw materials in credit at PT. Prometama Sarana Graha which is currently not computerized. System for purchasing raw materials at PT. Prometama Sarana Graha Still manual, from the process of ordering raw materials to making reports. Computerization of the system is the best solution to solve the problems that exist in PT. Prometama Sarana Graha, And with a computerized system can be achieved an effective and efficient activity in supporting activities at PT. Prometama Sarana Graha, and can reduce the buildup of archives at PT. Prometama Sarana Graha.